2020
DOI: 10.1149/1945-7111/abc723
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Coreduction of Gd(III) with Pb(II) and Recovery of Gd from LiCl-KCl Eutectic Assisted by Pb Metal

Abstract: To recover Gd from LiCl-KCl eutectic, the coreduction mechanism of Gd(III) with Pb(II) was investigated using electrochemical methods. The formation potentials related to the formation of three Gd-Pb intermetallics were detected by cyclic voltammetry, square wave voltammetry and chronopotentiometry, and the formation mechanism of Gd-Pb compounds could be described as xPb(II) + 2xe− = xPb. Meanwhile, the electroreduction of Gd on liquid Pb electrode was explored. The diffusion coefficient of Gd metal in liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Three pairs of reaction peaks (A/A 0 , C/C 0 and B/B 0 ) observed from the black curve are attributed to the reduction/oxidation of metal Li, metal Bi and Bi-Li intermetallic compound, 25,26 while three new reduction peaks (D, E and F) detected at À2.03, À1.59 and À1.29 V on the red curve are associated with the formation of metal Gd and Gd-Bi alloys. 27,28 To further investigate the generation of Gd-Bi alloys, CVs with various potential windows were conducted in LiCl-KCl-BiCl 3 -GdCl 3 melt. Fig.…”
Section: Co-deposition In Licl-kcl-gdcl 3 -Bicl 3 Meltmentioning
confidence: 99%
“…Three pairs of reaction peaks (A/A 0 , C/C 0 and B/B 0 ) observed from the black curve are attributed to the reduction/oxidation of metal Li, metal Bi and Bi-Li intermetallic compound, 25,26 while three new reduction peaks (D, E and F) detected at À2.03, À1.59 and À1.29 V on the red curve are associated with the formation of metal Gd and Gd-Bi alloys. 27,28 To further investigate the generation of Gd-Bi alloys, CVs with various potential windows were conducted in LiCl-KCl-BiCl 3 -GdCl 3 melt. Fig.…”
Section: Co-deposition In Licl-kcl-gdcl 3 -Bicl 3 Meltmentioning
confidence: 99%
“…Compared with the solid cathode, the liquid metal cathode has been widely studied because of its constant surface area and easy diffusion of deposits to liquid metal. Jiao et al [24] summarized liquid metals from the aspects of properties, depolarization effects, alloy preparation, etc., such as liquid Bi [25][26][27][28], Pb [29][30][31][32], Sn [33][34][35][36], and Ga [37][38][39][40], which provided a reference for molten salt electrorefining.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Therefore, it is critical to recover and separate lanthanides from molten salt for nuclear fuel cycle and the purification of waste salts. 29 In recent years, the electrorecovery lanthanides from molten salt were explored on various electrodes, for example, Mg, 30 Al, [31][32][33][34] Ni, 35,36 Cu, [37][38][39] Bi, [40][41][42][43] Zn, 38,39,44,45 Cd, 46,47 Sn, 48 Pb, [49][50][51] and Ga. 52 Since there are some advantages to use low melting point metal as a liquid working electrode, many researchers paid more attentions to the electrochemical extraction using a liquid electrode. Our group investigated the electroextraction of Tb and Y from molten chloride using solid Cu and liquid Zn as working electrodes and found that under same conditions, metallic Y and Tb easily deposited on liquid Zn electrode.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is critical to recover and separate lanthanides from molten salt for nuclear fuel cycle and the purification of waste salts 29 . In recent years, the electrorecovery lanthanides from molten salt were explored on various electrodes, 30‐51 for example, Mg, 30 Al, 31‐34 Ni, 35,36 Cu, 37‐39 Bi, 40‐43 Zn, 38,39,44,45 Cd, 46,47 Sn, 48 Pb, 49‐51 and Ga 52 . Since there are some advantages to use low melting point metal as a liquid working electrode, many researchers paid more attentions to the electrochemical extraction using a liquid electrode.…”
Section: Introductionmentioning
confidence: 99%